Air Transport System - Schmitt, Dieter; Gollnick, Volker; SpringerLink (Online service) (Vienna : Springer Vienna : Imprint: Springer, 2016)
The book addresses all major aspects to be considered for the design and operation of aircrafts within the entire transportation chain. It provides the basic information about the legal environment, which defines the basic requirements for aircraft design and aircraft operation. The interactions between airport, air traffic management and the airlines are described. The market forecast methods and the aircraft development process are explained to understand the very complex and risky business of an aircraft manufacturer. The principles of flight physics as basis for aircraft design are presented and linked to the operational and legal aspects of air transport including all environmental impacts. The book is written for graduate students as well as for engineers and experts, who are working in aerospace industry, at airports or in the domain of transport and logistics.
The air transport system. -- Historical development of air transport -- Market aspects -- The regulatory framework of the air transportation System -- Aircraft characteristics -- Aircraft manufacturer -- Airlines -- Airport and Infrastructure -- Air Navigation Services -- Environmental aspects of air Transport -- Challenges and competition of air Transport.
Keywords: Aerospace engineering; Astronautics; Security systems; Industrial Management; Technological innovations; Aerospace Technology and Astronautics; Security Science and Technology; Industrial Management; Innovation and Technology Management